2007
DOI: 10.4054/demres.2007.17.29
|View full text |Cite
|
Sign up to set email alerts
|

First child of immigrant workers and their descendants in West Germany

Abstract: This paper investigates the impact of immigration on the transition to motherhood among women from Turkey, Italy, Spain, Greece, and the former Yugoslavia in West Germany. A hazard-regression analysis is applied to data of the German SocioEconomic Panel study. We distinguish between the first and second immigrant generation. The results show that the transition rates to a first birth of first-generation immigrants are elevated shortly after they move country. Elevated birth risks that occur shortly following t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
142
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(153 citation statements)
references
References 54 publications
6
142
0
5
Order By: Relevance
“…If intermarriage is rare, it may not be an ideal measure of social distance (Sassler & Qian, 2003). Studies of fertility behavior have demonstrated that the act of migration is often closely bound up with family formation processes (Milewski, 2007;Stephen & Bean, 1992), and so it too may be a flawed measure of family change among first generation immigrants (Andersson, 2004;Sobotka, 2008;Toulemon, 2004).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…If intermarriage is rare, it may not be an ideal measure of social distance (Sassler & Qian, 2003). Studies of fertility behavior have demonstrated that the act of migration is often closely bound up with family formation processes (Milewski, 2007;Stephen & Bean, 1992), and so it too may be a flawed measure of family change among first generation immigrants (Andersson, 2004;Sobotka, 2008;Toulemon, 2004).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Moreover, in the case of migrants, ideals may be a particularly useful measure of attitudes toward the family life course since the timing of actual family behaviors is often distorted by the act of migration (e.g. Andersson, 2004;Milewski, 2007;Toulemon, 2004). The perceived ideal timing of family events is governed by attitudes and values, and is transmitted at multiple levels, through family and community socialization, and institutions.…”
mentioning
confidence: 99%
“…Por otro lado, están los trabajos que se centran en analizar las variaciones en el comportamiento reproductivo durante su período de estancia en la sociedad de destino, destacando diferentes patrones: los que apuntan a un proceso de «asimilación-adaptación» que predice que los inmigrantes gradualmente ajustan su comportamiento reproductivo al del país de destino (Kahn 1988(Kahn y 1994Andersson 2004;Parrado y Morgan 2008); los que, por el contrario, encuentran que ciertos grupos de inmigrantes tienden a «mantener» las normas y patrones reproductivos del país de origen (AbbasiShavazi y McDonald 2002), señalando que la falta de adaptación puede ser explicada por la existencia de un proceso de «selección» entre los migrantes (Goldstein 1973;Abbasi-Shavazi y McDonald 2000;Feliciano 2005; Bledsoe, Houle y Sow 2007); finalmente, otros estudios han constatado la existencia de un proceso de «interrup-ción-ruptura» en la fecundidad de la población inmigrante causado por el momento de migración y la separación de los esposos (Ford 1990;Stephen y bean 1992;Carter 2000;toulemon 2004;Kulu 2005;Lindstrom y Giorguli 2007;Milewski 2007).…”
Section: Marco Teórico E Hipótesisunclassified
“…The first examines determinants of inter-ethnic marriage among immigrants and their descendants (Alba and Golden 1986;Bagley 1972;Berrington 1994;Coleman 1994;Kalmijn 1998;Pagnini and Morgan 1990), and the second investigates childbearing patterns (Dinkel and Lebok 1997;Schoorl 1990). While both research streams have a long tradition, the increased availability of individual-level longitudinal data in the past two decades has boosted research activity in these areas and significantly enhanced our understanding of immigrant and ethnic minority family behaviour (Andersson 2004;González-Ferrer 2006;Milewski 2007;Singley and Landale 1998).…”
Section: Advances In Research On Immigrant and Ethnic Minority Familiesmentioning
confidence: 99%